A tentative model of Andhi - JOSEPH, P. V. (MAUSAM, 1982)
Based on the thunderstorm downdraft model developed by Charba (1974) and Goff (1976), a tentative model of Andhi (the convective duststorm of northwest India) has been suggested. This model is able to explain qualitatively the visibility variations in atypical type-1 Andhi(The details of visibility variations in the four types of Andhi have been given by Joseph et al. 1980). The slower visibility improvement and the consequent longer duration of type-2 (night time) Andhi also gets a logical explanation, if one assumes that the Andhi ’head’ moves forward more slowly at night, when the ambient air-density is higher. This assumption has theoretical support from studies on the propagation of ’gravity current’ heads.